2020
DOI: 10.5430/ijfr.v11n2p128
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Knowledge, Promotion, and Religiosity on Intention to Use Islamic Banking Services

Abstract: This study aims to examine the effect of knowledge, promotion, and religiosity on the interest in using Islamic banking services. The purpose of the next research is to examine the effect of knowledge on religiosity. In addition, this study also examines the effect of educational background and age on saving interest in Islamic banks. The population in this study are customers of Bank Syariah Mandiri, Brebes, Central Java, Indonesia. Ninety-nine research samples were obtained. The data collection method used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…Hence, such similarities are required to be combined under a single factor to avoid repetition in terms of their nature and concept. Similar treatment is also found in the existing literature where multiple factors are grouped into a single factor (Abduh et al , 2018; Abdul Rehman and Masood, 2012; Ahmad et al , 2011; Ali et al , 2018; Amin 2017a, 2019; Amin et al , 2009; Bizri et al , 2018; Butt et al , 2018; Echchabi and Azouzi, 2015; Gerrard and Barton Cunningham, 1997; Iqbal et al , 2018; Ismail et al , 2014; Jamshidi and Hussin, 2016; Januri et al , 2011; Kaakeh et al , 2018, 2019; Nurkhin et al , 2020; Kontot et al , 2016; Kumar et al , 2009; Lujja et al , 2018; Maulana et al , 2018; Shafie et al , 2004; Zabri and Mohammed, 2018).…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…Hence, such similarities are required to be combined under a single factor to avoid repetition in terms of their nature and concept. Similar treatment is also found in the existing literature where multiple factors are grouped into a single factor (Abduh et al , 2018; Abdul Rehman and Masood, 2012; Ahmad et al , 2011; Ali et al , 2018; Amin 2017a, 2019; Amin et al , 2009; Bizri et al , 2018; Butt et al , 2018; Echchabi and Azouzi, 2015; Gerrard and Barton Cunningham, 1997; Iqbal et al , 2018; Ismail et al , 2014; Jamshidi and Hussin, 2016; Januri et al , 2011; Kaakeh et al , 2018, 2019; Nurkhin et al , 2020; Kontot et al , 2016; Kumar et al , 2009; Lujja et al , 2018; Maulana et al , 2018; Shafie et al , 2004; Zabri and Mohammed, 2018).…”
Section: Methodssupporting
confidence: 68%
“…The previous studies are also in agreement with the results, like Mufraini et al (2020) analyzed promotion as an important factor that attracts the emotions of an individual and affects customer’s decision to use Islamic bank. Nurkhin et al (2020) proved promotion has a significant and positive impact to patronize Islamic banking. The research of Nemati et al (2018) showed advertisement as a positive influencer for attracting toward Islamic banking in Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…This research proves that knowledge of the prohibition of bank interest cannot strengthen the relationship, but knowledge of the customers about the fatwa should play an important role in shaping the religious motive of the customers. When customers have a better understanding of the rules of Islamic banking, it will increase their religiosity (Kardoyo et al, 2020).…”
Section: Results and Discussion Resultsmentioning
confidence: 99%
“…It also has no bearing on the relationship between the selection of Shariah banks by customers and the products and visuals they saw (Ichwan et al, 2021). Other studies from various other contexts generated similar outcomes (Amin et al, 2011;Kusumawardhini et al, 2016;Khan et al, 2019;Kardoyo Nurkhin et al, 2020), suggesting that religiosity is not necessarily a significant predictor and may not always impact users' adoption of technology.…”
Section: Religious Commitment and Consumer Intentionmentioning
confidence: 93%